Cities in the World: 1500-2000: v. 3 - Green, Adrian, author.
1 online resource (332 pages)
Keywords: Papers presented at the Cities in the World conference held at Southampton University and organised through the Society for Post-Medieval Archaeology challenged the commonly held perception that cities are about the present and the future, not about the past.